Does Increased Exposure to Peers with Adverse Characteristics Reduce Workplace Performance? Evidence from a Natural Experiment in the US Army - Murphy, Francis X. (Journal of Labor Economics, 2019)
While much research has investigated peer effects in education, less is known about peer influence at work, particularly how bad peers affect other workers. I study soldiers during a time when the US Army granted large numbers of morality waivers to recruits with felony or misdemeanor convictions that normally preclude enlistment. I find that soldiers randomly assigned to larger shares of peers with criminal backgrounds are more likely to commit major misconduct. Additionally, that misconduct often occurs in the same month a waivered peer commits misconduct, suggesting that influence occurs through both exposure to adverse peers and their contemporaneous behavior.